The Kurdish Movement’s Factor in US Politics at the Peak of Iran and Afghanistan Crises, 1979 – January 1981 - V. T. Yungblud; A. I. Sennikov (Vestnik MGIMO-Universiteta)
At the close of 1979, the United States encountered a critical need to realign its Middle East strategy in the wake of the capture of the American Embassy in Tehran by supporters of Iran's Supreme Leader, Ayatollah R. Khomeini on November 4, and the subsequent deployment of Soviet troops in Afghanistan on December 25. Faced with the challenges presented by the Iranian and Afghan crises, the United States' analytical, intelligence, and military bodies navigated various resources in search of viable solutions.This study delves into the consideration of the Kurdish factor as a potential instrument in shaping the regional landscape. The National Security Council (NSC), State Department, Central Intelligence Agency (CIA), and the US Department of Defense all scrutinized the Kurdish movement, evaluating its prospects for advancing American interests. Drawing from documents obtained from the State Department, National Security Council, and CIA, this article tracks the evolution of US policy concerning the Kurdish movement and its utility in realizing Washington's strategic objectives during the most critical phases of the Iran and Afghanistan crises.The analysis underscores the fundamental flaw in the initial evaluation of events in Afghanistan and Iran, misinterpreting them as a calculated move within a Soviet strategy to extend influence into the Persian Gulf region. This misconception was the primary cause of the Carter administration's failure in utilizing the Kurds as a counterforce against the Khomeini regime and its erroneous perceptions of the Iranian political regime's vulnerabilities. Inconsistencies in Washington's relationship with Tehran hindered the formulation of a coherent approach toward the Afghan-Iranian direction.